Transjugular Intrahepatic Portosystemic Shunt Placement for Refractory Ascites: Review and Update of the Literature - Burgos, Ana Cecilia; Thornburg, Bartley (Seminars in Interventional Radiology, 2018)
Ascites is the most common complication of cirrhosis, impairs quality of life, and carries a poor prognosis. Transjugular intrahepatic portosystemic shunt (TIPS) is a well-validated therapy for refractory ascites and is superior at reducing the accumulation of fluid compared with paracentesis. More recent evidence has shown that TIPS also provides an improved transplant-free survival compared with paracentesis. To maximize the clinical efficacy and survival advantage, proper patient selection is crucial. While current guidelines recommend that elective TIPS for ascites should be performed only in patients with MELD ≤ 18, recent literature suggests that elective TIPS safely and effectively controls ascites and potentially provides a survival advantage in patients with higher MELD scores (≤ 24). The evolution of these findings likely represents the combination of improved medical management of cirrhotic patients, improved devices, and a better knowledge of selection criteria for potential TIPS patients. This article will review the pathophysiology and management of ascites, with a focus on the evidence supporting TIPS placement for refractory ascites.
Keywords: TIPS; portal hypertension; refractory ascites